Tinjauan Yuridis Mengenai Batasan Pertanggungjawaban Profesi Notaris Terkait Dengan Penerapan PMPJ - Fadhillah Azhari; Junior B. Gregorius; Khalimi . (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the juridical limits of notary professional liability in implementing the Know Your Customer Principle (PMPJ). The issue arises from normative conflicts between the notary’s obligation to apply PMPJ under Ministerial Regulation No. 9 of 2017 and the confidentiality principle mandated by the Law on Notary Office (UUJN). This research addresses two main questions: (1) the legal boundaries of notary responsibility concerning client identity verification, and (2) legal protection mechanisms for notaries against unlawful acts committed by clients. This research applies a normative juridical method using statutory and conceptual approaches, supported by theories of justice, contract theory, and legal liability theory. The findings indicate that notarial responsibility is limited to formal verification (formal truth), and notaries cannot be held liable for material falsifications conducted by clients beyond their knowledge and authority. Furthermore, regulatory reconstruction is necessary to provide professional immunity and legal certainty to prevent criminalization risks.